Between support and strain: How do the illness narratives of patients with mental issues articulate the affordances of smartphones? - Zizhong Zhang; Qing Huang (Digital Health)
Objective This study explores how smartphones are depicted in the illness narratives of patients with mental health issues, focusing on the roles smartphones play and their affordances within online depression communities. Methods We analyzed discussions from an online depression group with over 60,000 members using Semantic Network Analysis (SNA) and Critical Discourse Analysis (CDA). Results The study identified three key roles of smartphones—as information brokers, communication tools, and emotional valves—which correspond to affordances of visibility, connectivity, and persistence. These affordances both facilitate and constrain behaviors in illness narratives, revealing a double-edged sword effect where smartphones provide essential support and emotional relief but also exacerbate negative experiences such as anxiety and rumination. Conclusion The findings bridge affordance theory and online narrative studies, deepening the understanding of media technologies’ interplay with mental health. This study offers insights into how smartphone affordances shape lived experiences, contributing to the development of digital narrative therapy.